2020
DOI: 10.1098/rstb.2019.0814
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for building out mosquito-transmitted diseases in sub-Saharan Africa: the DELIVER mnemonic

Abstract: In sub-Saharan Africa, most transmission of mosquito-transmitted diseases, such as malaria or dengue, occurs within or around houses. Preventing mosquito house entry and reducing mosquito production around the home would help reduce the transmission of these diseases. Based on recent research, we make key recommendations for reducing the threat of mosquito-transmitted diseases through changes to the built environment. The mnemonic, DELIVER , recommends the following best practices: (i) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 79 publications
1
30
0
Order By: Relevance
“…Raising houses off the ground, like any intervention, is not evolutionary proof, and over time, mosquitoes may adapt and feed higher off the ground than before. Nonetheless, we recommend elevating houses off the ground since they are likely to reduce mosquito biting and keep the occupants cooler at night [7] and therefore more likely to use an ITN. This research is likely to be relevant to many hot and humid parts of sub-Saharan Africa where An.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raising houses off the ground, like any intervention, is not evolutionary proof, and over time, mosquitoes may adapt and feed higher off the ground than before. Nonetheless, we recommend elevating houses off the ground since they are likely to reduce mosquito biting and keep the occupants cooler at night [7] and therefore more likely to use an ITN. This research is likely to be relevant to many hot and humid parts of sub-Saharan Africa where An.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a meta-analysis of 29 malaria surveys carried out in 21 sub-Saharan African countries between 2008 and 2015 found that modern housing was associated with a 9-14% reduction in the odds of malaria infection when compared with traditional housing, a level of protection comparable to ITNs in the same study [6]. Modern houses are more likely to have closed eaves (the gap between the top of the wall and the overhanging roof ), and screened windows and doors, all modifications known to reduce the entry of malaria mosquitoes into houses [7]. Completely closing a building in the hot humid tropics, however, will reduce ventilation and increase the temperature of the house before midnight, particularly if the roof is metal [8,9].…”
Section: Introductionmentioning
confidence: 88%
“…Ultimately, whether a metal-roof house has more or less mosquitoes than a thatch-roof house will depend on how porous the house is to mosquitoes and the extent of ventilation [ 16 ]. Further research is needed to understand the importance of different house construction features on indoor climate and vector entry.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that malaria mosquito house entry can be reduced through simple changes to house design, such as closing eaves and screening windows and doors [ 16 ]. The use of personal protective measures such as ITNs and spatial repellents may also reduce transmission [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lindsay et al [30] explore relatively simple changes to the built environment, including the installation of tight-fitting screened doors, the closing or screening of eaves and replacement of thatched roofs with roofs made from solid materials, such as metal or tile. An important message is to combine a package of interventions for maximum impact.…”
Section: Household-level Vector Control Toolsmentioning
confidence: 99%